Edukasi dan Pendampingan Pengelolaan Sampah untuk Mewujudkan Lingkungan Bersih dan Sehat di Desa Tenggela Kecamatan Tilango Kabupaten Gorontalo - Muh. Khaedir (Paramacitra Jurnal Pengabdian Masyarakat, 2026)
Household waste remains a major challenge in maintaining environmental quality and public health. Low levels of knowledge, skills, and community participation in waste management have led to an increase in the volume of waste disposed of without sorting, leading to environmental pollution and disease risks. This community service activity aims to increase public knowledge and awareness regarding the importance of proper waste management, improve skills in sorting and processing organic and inorganic waste, encourage the utilization of waste into useful and economically valuable products, and create a clean, healthy, and sustainable environment through active community participation. The implementation method included initial identification through observation, interviews, and pre-tests, followed by education, practical training, mentoring, and evaluation using post-tests and field observations. The activity was attended by 30 participants, consisting of housewives, youth, and community leaders. The results showed that the average knowledge score of participants increased from 56.4 in the pre-test to 89.1 in the post-test. Ninety percent of participants were able to sort waste correctly, 80% successfully made simple compost, and 70% produced craft products from inorganic waste. Furthermore, community participation has increased, and environmental conditions have become cleaner and more organized. This program has proven effective in increasing community capacity in waste management based on the 3R principles (Reduce, Reuse, Recycle) and a circular economy. Participatory education and mentoring have encouraged changes in community behavior and built a shared commitment to maintaining a clean environment sustainably. This program is recommended for replication in other regions with support from the government, universities, and the community to ensure continued environmental, social, and economic benefits.